Integrated Project Teams: The MoD's New Hot Potato? - Moore, David M.; Antill, Peter D. (Taylor & Francis, 2000)
Since the announcement of Smart Procurement, much has been written on the potential benefits that IPTs will hopefully bring. It is supposed that they will improve the interface with industry, create a better understanding of requirements and establish an environment where industry is motivated to perform and so reduce cost, risk and time into service while improving product quality. The formation of a team should provide continuity, consistency, flexibility and ~ increased performance due to the integration of a wide-range of functional activities and decision-making, as well as increased motivation. These may well be gallant objectives, but how achievable are they? What obstacles does the MoD face in the implementation of the IPTs? Have they grasped a 'hot potato'?